Parents’ Perspectives towards Transition of Children with SEND from Early Intervention to other Educational Settings - Abdat, Rawhi (2020)
The purpose of the study was to investigate parents’ perspectives and roles in the transition process from ECI to other educational contexts, and to understand how educational policies empower parents and support their children with SEND during the transition. Therefore, the study followed a sequential exploratory mixed-methods design to collect both qualitative and quantitative data. Data was primarily collected using semi-structured interviews with eleven parents of children with different types of SEND and content analysis to the early education policies. Questionnaires administered to (183) parents in Dubai, Ajman, Ras Al Khaimah and Fujairah in the UAE. Thematic analysis of interviews was conducted and found that parents perceive the transition process through three main categories as: 1) blurring 2) stressful 3) smooth. While they view their roles as: 1) ambiguous 2) active 3) no role 4) roles they should do. Thematic analysis of educational policies showed two main categories: 1) parents’ empowerment 2) children inclusion. Moreover, descriptive and inferential statistical analysis tests were performed using SPSS software of the parents’ responses to the cross-sectional survey showed significant differences among parents’ perspectives towards transition with respect to parents’ gender, parents’ education, type of child with SEND, the educational setting and the Emirate, however, no significant differences found in regards to the child gender. Finally, the study has several implications for early childhood intervention and policy in the UAE and the region as it draws a road map for children transition trajectory to inclusive settings from parents’ perspectives.